Person-centred simulation of product development processes. (17th December 2007) - Licht, Torsten; Schmidt, Ludger; Schlick, Christopher M.; Dohmen, Lothar; , Holger Luczak
In enterprises with multiple projects, product developers often fail to act according to project plans, even though the plans have been developed very thoroughly. The proposed person-centred simulation model can simulate more realistic courses of development projects. A major difference to existing models is the bounded rational decision making of the simulated product developers. The model was formally described by Timed Stochastic Coloured Petri Nets and was systematically verified using an analysis of variance. The results of a case study in a medium-sized enterprise show that the simulated project durations do not significantly differ from the historical data.